The Effect of Using Think Pair Share to Improve Students’ Reading Skills - Santi Rosalia; Olyvia Revalita Candraloka (J-SHMIC : Journal of English for Academic, 2023)
Reading is an active process of getting information and understanding from printed text media. Reading is one of the most important skills in language learning. Reading has challenges for many students; most students find it difficult to understand the topic of the text. Then, students are also passive in class. So, they couldn’t answer the question properly. Therefore, the teachers are expected to use a learning model that can overcome the problems in reading. This research aims to find out the effectiveness of Think Pair Share to improve students’ reading skills. This study was conducted at tenth grade students of MA Shofa Marwah which consist of 36 students. This research was quantitative research using quasi-experimental design with pre-test and post-test design. The data were collected through test in the form of multiple choice test. The mean score of the students in the experimental group was 88 while the mean score of the students in the control group was 72.19. The T-Test analysis showed that Sig. (2-tailed) was 0.000 which was less than 0.05 and the T-Test was more than T-table (8.514 > 2.04). The result indicated that the use of Think Pair Share was effective toward students’ reading achievement.